Intraperitoneal Onlay Mesh in Ventral Hernia Repair Experience in A Tertiary Care Hospital in Bangladesh (BIRDEM Medical Journal, 2017)
Background: Ventral hernias are common problem in surgical practice. Repair of hernia by a prosthetic mesh is a well recognized procedure. But whether the procedure is to be done by open or laparoscopic technique is still a topic of discussion. Laparoscopic intraperitoneal onlay mesh (IPOM) hernioplasty is a newer technique in managing ventral hernia in our country. We are evaluating the usefulness of this procedure as routine operation for ventral hernias.Methods: All patients attending at Bangladesh Institute of Research & Rehabilitation of Diabetes, Endocrine and Metabolic disorders (BIRDEM) outpatient department (OPD) with ventral hernia were approached and counseled for laparoscopic IPOM, but only those who agreed were included in this study. Fifty consecutive patients underwent IPOM by a single surgeon. Preoperative evaluation was done rationally and surgery performed by standard laparoscopic method. Age, sex, diabetes status and additional procedures done were evaluated. Post- operative follow up period was from 3 months to 75 months and any complication or recurrence were noted.Results: We are reporting 50 cases of laparoscopic IPOM, over a time period of 78 months (April 2010- September 2016). Eleven cases were male, 39 female (M: F=1:3.5). 35 (70%) cases were diabetic, 15 (30%) were non-diabetic. Mean age of the patients were 47.7yrs (male 47.7+9.5 yrs, female 47.7- 2.6 yrs, diabetic patients 47.7+ 2.5yrs, non-diabetic patients 47.7-5.9yrs). Indication for IPOM was paraumbilical hernia 29 cases (58%), incisional hernia 14 cases(28%), multiple incisional hernia 2 cases ( 2 large defect in one case, 5 defects of varying size in another patient), umbilical port hernia 2 cases, paraumbilical along with incisional hernia 1 case, epigastric hernia 1 case, lumber hernia 1 case. In 48 cases (96%) polypropylene mesh and only in 2 cases (4%) dual mesh were used. In addition to IPOM procedure, in same sitting laparoscopic cholecystectomy was done in 8 cases, Dilatation & Curettage in 1 case and adhesiolysis in 7 cases. None of the case required conversion to open, neither was there any intra-operative complication. In one case there was recurrence . In another case there was false recurrence due to development of ascites. Four patients developed seroma which were managed conservatively.Conclusion: Laparoscopic intraperitoneal onlay mesh (IPOM) hernioplasty has proved to be an effective surgical procedure for ventral hernia repair. It provides much benefits with low complications and conversion in experienced hands.Birdem Med J 2017; 7(2): 106-109